Exposure of Estrus Female and its Urine Improves Semen Quality Profiles and Freezabilityin Mithun - Perumal, P. (International Journal of Bio-resource and Stress Management, 2018)
Effect of different methods of biostimulation on semen quality profiles (SQPs) and freezability and endocrinological profiles in mithun bulls was studied. Twelve adult healthy mithun bulls (4 to 5 years) with good body condition (score 5-6)were selected from mithun breeding farm, ICAR-NRC on Mithun, Medziphema, Nagaland, India. Biostimulation methods were categorised into four groups and each group consisted of three animals, viz. Gr I: exposure of non-estrus female, Gr II: exposure of urine of non-estrus female, Gr III:exposure of urine of estrus female and Gr IV: exposure of estrus female. These bulls were bio-stimulated once in 5 days for two months (total 12 visits) of the respective group. Semen samples were collected after 12 visits and before collection, the female or its urine is exposed to bulls in every time. A total of 40 semen samples (10 from each group) were collected by transrectal massage method and SQPs, velocity and motility parameters were measured. Blood samples were collected immediately after exposure and hormone profiles such as follicle stimulating hormone (FSH), luteinizing hormone (LH) and testosterone were analysed by using commercial diagnostic kits. Result revealed that significant (p<0.05) difference was observed among the methods of biostimulationfor all theexperimental parameters. Of which, highest value was observed in bulls exposed to estrus female or its urine than non-estrusfemales or its urine. Therefore, it was concluded that exposure of estrus cows or its secretions have capability to increase the semen production and the sperm has higher freezability in mithun.